Moderasi Beragama dalam Perspektif Tindakan Sosial Max Weber - Sumintak Sumintak; Iin Ratna Sumirat (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article discusses Max Weber's thoughts on social actions which are assumed to contribute to radical behavior. The thought will be related to the concept of religious moderation as one of the most important things in understanding one's religious actions. This article is a library research that examines various existing literature such as books, magazines, documents, and historical records, this is a series of activities carried out in order to collect library data or study literature on social actions in the context of religious moderation. using an interpretative phenomenological approach. The results of this study indicate that there are four types of social action that can be harmonized in religious moderation, namely traditional action, affective action, instrumental rationality, and value rationality. If religious people implementation the pattern of these four actions by combining them, then the understanding of religious moderation will be quickly understood by all religious people so that it can provide comfort and peace when carrying out religious activities in the reality of everyday life.Artikel ini membahas tentang pemikiran Max Weber tentang tindakan sosial yang diasumsikan turut membentuk prilaku radikal. Pemikiran tersebut akan dihubungkan dengan konsep moderasi beragama sebagai salah satu hal terpenting dalam memahami tindakan keberagamaan seseorang. Artikel ini merupakan kajian kepustakaan (library research) yang menelaah berbagai literatur yang ada seperti buku, majalah, dokumen, dan catatan-catatan sejarah, ini merupakan serangkaian kegiatan yang dilakukan dalam rangka melakukan pengumpulan data kepustakaan atau kajian literatur tentang tindakan sosial dalam konteks moderasi beragama menggunakan pendekatan fenomenologi interpretative. Hasil penelitian ini menunjukkan bahwa ada empat tipe tindakan sosial yang dapat diselaraskan dalam moderasi beragama yaitu tindakan tradisonal, tindakan afektif, rasionalitas instrumental, rasionalitas nilai. Apabila umat beragama menerapkan pola keempat tindakan tersebut dengan mengkombinasikannya maka pemahaman terhadap moderasi beragama akan begitu cepat dipahami oleh semua umat beragama sehingga dapat memberikan kenyamanan dan ketentraman saat menjalankan aktifitas kegamaan dalam realitas kehidupan sehari-hari.